Internationalisms a twentieth-century history - Sluga, Glenda 1962-; Clavin, Patricia 1964- (Cambridge University Press, 2017)
This is a pioneering survey of the rise of internationalism as a mainstream political idea mobilised in support of the ambitions of indigenous populations, feminists and anti-colonialists, as well as politicians, economists and central bankers. Leading scholars trace the emergence of intergovernmental organisations such as the League of Nations, the United Nations, the International Labour Organisation and the World Health Organisation, and the corresponding expansion in transnational sociability and economic entanglement throughout the long twentieth century. They reveal how international thought helped to drive major transformations in the governance of global issues from refugees to slavery and sex-trafficking, from the environment to women's rights and human rights, and from state borders and national minorities to health, education, trade and commerce. In challenging dominant perceptions of how contemporaries thought of nations, states and empires, Internationalisms radically alters our understanding of the major events and ideas that shaped twentieth-century politics, culture, economics and society